Hands-On Defibrillation Skills of Pediatric Acute Care Providers During a Simulated Ventricular Fibrillation Cardiac Arrest Scenario - Bhalala, Utpal S.; Balakumar, Niveditha; Zamora, Maria; Appachi, Elumalai (Frontiers in Pediatrics, 2018)
Introduction: Timely defibrillation in ventricular fibrillation cardiac arrest (VFCA) is associated with good outcome. While defibrillation skills of pediatric providers have been reported to be poor, the factors related to poor hands-on defibrillation skills of pediatric providers are largely unknown. The aim of our study was to evaluate delay in individual steps of the defibrillation and human and non-human factors associated with poor hands-on defibrillation skills among pediatric acute care providers during a simulated VFCA scenario. Methods: We conducted a prospective observational study of video evaluation of hands-on defibrillation skills of pediatric providers in a simulated VFCA in our children's hospital. Each provider was asked to use pads followed by paddles to provide 2 J/kg shock to an infant mannequin in VFCA. The hands-on skills were evaluated for struggle with any step of defibrillation, defined a priori as >10 seconds delay with particular step. The data was analyzed using chi-square test with significant p-value <0.05. Results: A total of 68 acute care providers were evaluated. Median time to first shock was 97 sec (IQR: 60-122.5 sec) and did not correlate with provider factors, except previous experience with the defibrillator used in study. The number of providers who struggled (>10 seconds delay) with each of connecting the pads/paddles to the device, using pads/paddles on the mannequin and using buttons on the machine was 34 (50%), 26 (38%) and 31 (46%), respectively. Conclusions: The defibrillation skills of providers in a tertiary care children's hospital are poor. Both human and machine-related factors are associated with delay in defibrillation. Prior use of the study defibrillator is associated with a significantly shorter time-to-first shock as compared to prior use of any other defibrillator or no prior use of any defibrillator.